2011
DOI: 10.1161/atvbaha.111.223537
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Epidermal Growth Factor Receptor (ErbB1) Loss for Vascular Smooth Muscle Cells From Mice With Targeted Deletion of ErbB1

Abstract: Objective— Pathophysiological effects of the epidermal growth factor receptor (EGFR or ErbB1) include vascular remodeling. EGFR transactivation is proposed to contribute significantly to heterologous signaling and remodeling in vascular smooth muscle cells (VSMC). Methods and Results— We investigated the importance of EGFR in primary VSMC from aorta of mice with targeted deletion of the EGFR ( EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 62 publications
2
41
1
1
Order By: Relevance
“…[22][23][24][25][26] As demonstrated earlier, 22 EGFR expression was almost abolished in the aortas ( Figure 1A), indicating a deletion of EGFR in VSMC. This result was confirmed by primary culture of VSMC demonstrating a reduction to 10±5% compared with controls.…”
Section: Expression Of Erbb Receptors In Aortas and Hearts Of Egfr δ/supporting
confidence: 75%
See 3 more Smart Citations
“…[22][23][24][25][26] As demonstrated earlier, 22 EGFR expression was almost abolished in the aortas ( Figure 1A), indicating a deletion of EGFR in VSMC. This result was confirmed by primary culture of VSMC demonstrating a reduction to 10±5% compared with controls.…”
Section: Expression Of Erbb Receptors In Aortas and Hearts Of Egfr δ/supporting
confidence: 75%
“…This result was confirmed by primary culture of VSMC demonstrating a reduction to 10±5% compared with controls. 22 In lung, liver, and kidney, EGFR expression was unchanged (Table S2). In the heart, where the SM22 promoter is active during embryogenesis, 25,26 expression of EGFR was reduced by one third ( Figure 1A).…”
Section: Expression Of Erbb Receptors In Aortas and Hearts Of Egfr δ/mentioning
confidence: 99%
See 2 more Smart Citations
“…In a variety of cells, we and others have previously demonstrated that AT 1 R activation leads to phosphorylation of the ErbB1 receptor, downstream signalling and subsequent changes in cell physiology (Thomas et al, 2002;Ohtsu et al, 2006b). Moreover, deletion of ErbB1 in vascular smooth muscle cells reduces GPCR-mediated signalling and has marked effects on vascular and cardiac remodelling (Schreier et al, 2011;Schreier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%